Issues and Challenges in Implementing Care Coordinator in Primary Healthcare in Malaysia: A Qualitative Study - Zalilah Abdullah; Siti Hajar Abdul Aziz; Nur Aliyah Sodri; Ainul Nadziha Mohd Hanafiah; Nor Idawaty Ibrahim; Mohammad Zabri Johari (SAGE Publishing, 2020)
Background: Primary healthcare is the earliest gateway for patient care, and improvisations are often needed to accommodate the ever-increasing demand in public health. The Enhanced Primary Healthcare (EnPHC) initiative is aimed at improving such needs, and one core intervention is the introduction of a care coordinator (CC). The purpose of this study was to identify barriers and facilitators in implementing a new intervention in primary healthcare clinics. Methods: This qualitative exploration study. All healthcare providers who were involved in EnPHC at the intervention clinics were selected as participants. In-depth interviews and focus group discussions were carried out among healthcare providers working in the intervention clinic. Thematic analysis was used to categorize data, based on the consolidated framework for implementation research (CFIR) theoretical framework domains. Results: A total of 61 healthcare providers participated. All 5 domains with 19 CFIR constructs emerged from the analysis. Inner setting played a significant role in facilitating CC intervention, in which culture, networking, and collaboration and leadership engagement played an essential role in supporting CC activities. Although CC tasks are complex, concerns of losing clinical skill and resource constraints were identified as potential barriers in CC implementations. Criteria for appointing new CCs emerged from the characteristics of individual constructs, in which the individual must be familiar and interested in community health, have good communication skills, and at least 3 years' experience in the primary healthcare setting. Conclusion: The implementation of the CC intervention faces varying challenges in different settings. This is partially resolved through teamwork, guidance from mentors, and support from superiors. The complexity of the responsibility of the CC intervention is perceived as both a validation and a burden. Above all, it is seen as paramount in EnPHC intervention.